Tumors of the choroid plexus - (:unkn) unknown (Turkish Neurosurgical Society, 2002)
Objective: Choroid plexus neoplasms originate from choroid plexus epithelium. They are classified as papillomas and carcinomas histopathologically. The aim of this study is to discuss the signs, symptoms, treatment modalities and surgical results of this entities. Method: Ten cases of choroid plexus tumors operated on in Neurosurgery Department of Marmara University Medical School - İstanbul between 1992 and 2000, are presented with the review of literature. Radiological investigations of the patients are reevaluated. Patients operative, histopathological and postoperative follow up records are detected. Findings: One of the tumors was choroid plexus carcinoma and the others were choroid plexus papillomas. The youngest patient was two months old, the oldest one was 39 years old and the average age was 12,4. Female to male ratio was (5:5) one. Three patients were adults and the others were children. Major symptoms were headache, alteration in conscious level and enlargement of head. Most encountered neurological signs were papilla edema, alterations in conscious level, incrased head circumference and sixth nerve palsy. Five of the tumors (50%) were localized in the trigon of the lateral ventricle, three were in the fourth ventricle(30%) and one each in the third ventricle(10%) and in cerebellopontine angle (CPA) (10%). All of the tumors were excised totally except two. One of the residual mass was excised with reoperation and the gamma knife surgery was applied to the other one. Two patient died in early postoperative period. The others are still alive. Average postoperative follow up is 25 months. Conclusion: Total surgical excision is the most important prognostic factor for choroid plexus tumors.
Keywords: Carcinoma; Choroid plexus; Papilloma